Bilirubin and amyloid-beta peptide induce cytochrome c release through mitochondrial membrane permeabilization - Rodrigues, CMP (2015)
Background: The pathogenesis of bilirubin encephalopathy and Alzheimer's disease appears to result from accumulation of unconjugated bilirubin (UCB) and amyloid-beta (A beta) peptide, respectively, which may cause apoptosis. Permeabilization of the mitoch